HUBUNGAN ANTARA SELF REGULATED LEARNING DENGAN PROKRASTINASI AKADEMIK DIMASA PEMBELAJARAN DARING PADA SISWA KELAS XII SMA NEGERI 1 CIAWIGEBANG - Imatul Anam; Evi Srinur Hastuti; Anggian Heksa Efraim Sinaga (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2022)
Academic procrastination is a tendency to procrastinate activities related to academics. Students in the learning process need self-regulated learning abilities that help students manage thoughts, behaviors, and emotions so that they can successfully direct the learning process towards the learning goals to be achieved. The purpose of the study was to determine the relationship between self-regulated learning and academic procrastination during online learning in class XII students of SMAN 1 Ciawigebang. The research method used is the correlation method, which is to see the relationship between self-regulated learning variables and academic procrastination during online learning in class XII students of SMAN 1 Ciawigebang. The data collection technique used a questionnaire made in the form of google from. The measuring instrument for self-regulated learning variables is based on Zimmerman's theory (2011) and for academic procrastination variables based on McCloskey's theory (2011). The results showed that there was a negative and significant relationship between self-regulated learning and academic procrastination during online learning in class XII students of SMAN 1 Ciawigebang, with a value of rs = -0.800. The lower the self- regulated learning, the higher the academic procrastination in class XII students of SMAN 1 Ciawigebang. On the other hand, the higher the self-regulated learning, the lower the academic procrastination in class XII students of SMAN 1 Ciawigebang.